2016
DOI: 10.2174/1389200217666160322143504
|View full text |Cite
|
Sign up to set email alerts
|

Valproic Acid Metabolism and its Consequences on Sexual Functions

Abstract: VPA interferes with the endocrine system at multiples levels causing several reproductive and sexual dysfunctions in women and men with epilepsy, especially when administered in pubertal age. Since VPA is a first line AED both in children and adult with epilepsy and long-term medication with this drug is sometimes necessary, it is very important for physicians to implement strict monitoring of patients taking VPA in order to identify these kinds of side effects at an early stage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 0 publications
0
26
1
Order By: Relevance
“…It has been reported that the incidence of sexual dysfunction in male patients with epilepsy is 5 times higher than that in healthy people, and the incidence of sexual hyperactivity is about 2.9% . A number of studies have shown that epilepsy and AEDs (especially older AEDs) have a complex effect on male sex hormones, reproductive organs, and sexual function, leading to a decrease in fertility in male patients with epilepsy . In this study, the marriage rate and birth rate of the male adult patients with epilepsy were significantly lower than those of the healthy group, which may be related to the patients’ anxiety caused by seizures and different degrees of social discrimination.…”
Section: Discussionmentioning
confidence: 60%
See 3 more Smart Citations
“…It has been reported that the incidence of sexual dysfunction in male patients with epilepsy is 5 times higher than that in healthy people, and the incidence of sexual hyperactivity is about 2.9% . A number of studies have shown that epilepsy and AEDs (especially older AEDs) have a complex effect on male sex hormones, reproductive organs, and sexual function, leading to a decrease in fertility in male patients with epilepsy . In this study, the marriage rate and birth rate of the male adult patients with epilepsy were significantly lower than those of the healthy group, which may be related to the patients’ anxiety caused by seizures and different degrees of social discrimination.…”
Section: Discussionmentioning
confidence: 60%
“…There have also been studies reporting that when measuring the genital blood flow in patients with epilepsy, patients with temporal lobe epilepsy had less blood flow to the genitals; this may, to some extent, explain the sexual dysfunction . Newer AEDs (OXC, LEV, or LTG) might affect sexual function less than older AEDs . They can cause sexual dysfunction by affecting the secretion of sex hormones or by increasing the inhibition of GABA, inhibiting nerve conduction and reducing the transmission of sexual stimuli .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Decreased sexual desire and anorgasmia have also been described in bipolar women receiving valproate 140 . In men, valproate treatment may cause erectile dysfunction 141 .…”
Section: Influence Of Treatment Of Bipolar Disorder On Sexualitymentioning
confidence: 99%